Post-fire vegetation succession after 5 years in managed pine forests at different time since clearcutting - Gustafsson, Lena; Johansson, Victor; Leverkus, Alexandro; Strengbom, Joachim; Wikberg, Sofie; Granath, Gustaf (Swedish University of Agricultural Sciences, 2021)
To study plant community succession after fire and how it is influenced by time since previous (pre-fire) disturbance, vegetation data were collected in 2019, 5 years after a large (13000 hectare) wildfire in boreal Southern Sweden (county Västmanland). Plant communities were surveyed in severely burnt even-aged pine stands that varied in time since clearcutting (0-123 years) before the wildfire occurred. Data includes at the plot-level (50x50cm quadrats): vascular and moss species frequency, total cover, dead wood, and canopy openness. At the stand-level: means for all species, community weighted trait means (trait data from databases), and distance to the fire perimeter.

Two files are archived. (1) post_fire_vegetation_TSC_plotlevel_data.csv contains all raw data from each surveyed vegetation plot, (2) post_fire_vegetation_TSC_standlevel_trait_sp_data.csv contains averaged species abundance data and community weighted trait means at the stand level.

För att studera växtsuccessionen efter brand och hur den påverkas av successionstadiet när branden inträffade, samlades vegetationsdata in i västmanland fem år efter en stor brand (13 000 hektar boreal skog). I provytor inventerades växtsamhällena i hårt brända bestånd som varierade i ålder (0-123 år) sedan de hade kalhuggits innan brand. Data inkluderar på plot-nivå (50x50 cm provytor): kärlväxter och mossor, död ved, och krontäckets öppenhet (ljustillgänglighet). På beståndsnivå anges medelvärden för arter, viktad egenskapsdata (egenskapsvärden tagna från databaser), och avstånd till brandgränsen.
Fem år av vegetationssuccession efter brand i produktionsskogar av tall med olika beståndsålder
Data set: Shorter disturbance interval truncates vegetation succession
Keywords: Habitats and biotopes; Naturtyper och biotoper; Species distribution; Arters utbredning; boreal; boreal; forest fire; skogsbrand; plant community; växtsamhälle; clear cutting; kalhygge; tallskog; pine forest; plant traits; växtegenskaper; wildfire; vildbrand; resilience; resiliens; disturbance; störning; succession; succession; Botany; Botanik; Ecology; Ekologi; Forest Science; Skogsvetenskap; Biota; Biologi och ekologi